A17 HD brain-train: neuroplasticity as a target to improve function in huntington's disease. (13th September 2016) - Papoutsi, Marina; Weiskopf, Nikolaus; Langbehn, Douglas; Reilmann, Ralf; Rees, Geraint; Tabrizi, Sarah J
Abstract : Background and aims: The only approved treatment for Huntington's disease (HD) is Tetrabenazine for chorea, while there are no treatments for cognitive symptoms. Neurofeedback training, where patients are trained to regulate their own brain activity, could be used to support neurorestoration by targeting brain regions and networks whose function is impaired. The present study is the first to use real-time fMRI neurofeedback training in HD to establish whether patients can learn to regulate their brain activity and whether this will have a positive effect on behaviour. Methods and results: Ten patients were trained by receiving near real-time visual feedback about the level of activity of their supplementary motor area (SMA). All patients increased their SMA activity over time, however they differed in the degree to which they were able to regulate their brain activity volitionally after training. Improved performance in an unrelated motor task during upregulation compared to without predicted the degree of increased activity within the trained region during upregulation. This suggests that the ability to control brain activity could lead to control of motor performance. To evaluate the effects of training on behaviour we compared performance before and after training on a set of independent measures, sensitive to HD progression. Most (8 out of 10) participants improved, suggesting that the effects of training can be generalised. Improved performance predicted increased grey matter volume within the trained region, as well as increased coupling between the trained region and the striatum (left Putamen). This shows that using neurofeedback training we can stimulate functional and structural plasticity in HD patients with positive effects on cognitive and motor performance. Conclusions: Because rt-fMRI neurofeedback training is non-invasive, it can be used either preventatively or in conjunction with potential disease modifying therapies, to act as a dose regulator, or to boost brain re-organisation following e.g., HTT lowering therapy.